The Performance of Governance by ABC Mosque Management: A Case Study of Historic Jami' Mosques in the Special Region of Yogyakarta - Alwiyah, Jihan; Warsono, Sony; Suandi, Aprilia Beta; Muhammad, Muhammad (Journal of Accounting Inquiry, 2024)
Purpose: The purpose of this study is to gain a better understanding of mosque management practices from the perspective of stewardship theory. This research discusses the governance of routine and incidental activities that mosque management organizes. Methodology: This research uses a qualitative approach with a case study research design. The qualitative approach is used to gain an in-depth understanding of the phenomenon under study. In contrast, the case study design allows researchers to develop an in-depth analysis of the events that occur. Data were collected through in-depth interviews, observation, and document analysis. This research was conducted at two mosques in the Special Region of Yogyakarta, with the research subjects including mosque management (takmir). Findings: The research examined the management practices of Masjid ABC and found that it follows a traditional and simple governance structure. Applying stewardship theory is crucial to clarifying the dynamics of mosque fund management. Novelty: This research uses the stewardship theory perspective to see the resilience of traditional mosque management in maintaining its commitment to the congregation.